Fursemida Influence on glucose tolerance - Valdivia, Héctor (1969)
We have investigated the effect of Fursemida on glucose tolerance in 82 patients : 14 mormales , 15 cirrhotic , 15 diabetics, 7 patients with cardioesclerosis , 8 with hypertension , 8 nephropathy without failure and 15 with failure, for which administered daily 80 me . diuretic for one week. In 8 patients (4 diabetic , cirrhotic March 1 with hypertension ) occurred a pathological increase in basal glycemia. Except with nephropathy , elevated in all groups glycemia curves was observed , which was not significant in normal , diabetic , and cirrhosis . In cardiac patients the increase was noticeable but not statistically significant . In the hypertensive group the appearance of a greater number of abnormal curves was observed, mean difference at 90 ' and 120' was statistically significant. Patients with renal failure, most of whom had abnormal tolerances , showed declines and even normalization of tolerance curves after administration of Fursemida . These findings , although to a lesser extent , also observed in cases of nephropathy without failure. Abnormalities in tolerance curves showed no correlation with changes in serum electrolyte levels , uric acid , amylases, or with changes in body weight and urine volume . We discuss about the mechanisms of hyperglycemic Fursemida and other diuretics , as well as the paradoxical effect found in uremic . Special emphasis is placed on the possibility that intracellular electrolyte changes are responsible for the variations in the metabolism of carbohydrates produced by them. It concludes practical Fursemida that is a diuretic , which can be administered in patients with intolerance to hydrate carbon s no danger of decompensation occurs. Moreover it is necessary to take caution abnormal glucose curves in patients receiving Fursemida , since this does not necessarily mean that they are diabetic .